The treatment of the body image disturbances in eating disorders and clinically significant change. - Marco, Jose H.; Perpiñá, Conxa; Botella, Cristina (Anales de Psicología / Annals of Psychology, 2014)
Body image disturbance is a significant maintenance and prognosis factor in eating disorders. Hence, existing eating disorder treatments can benefit from direct intervention in patients’ body image. No controlled studies have yet compared eating disorder treatments with and without a treatment component centred on body image. This paper includes a controlled study comparing cognitive behavioral treatment for eating disorders with and without a component for body image treatment using virtual reality techniques. The objective of this work is to check if both types of treatment will produce a change clinically significant at the end of the treatment and the follow-up to the year. Thirty-four participants diagnosed with eating disorders were treated and compared with the general population with low vulnerability to eating disorders. Results showed that only in the patients who received the body image treatment obtained a change clinically significant. The implications and limitations of these results are discussed below.